High-entropy alloy soft magnetic composite material and preparation method and application thereof

By using high-entropy alloy powder and insulating layer coating technology with negative temperature coefficient, the problem of difficult to achieve low magnetic loss and temperature stability in the prior art under high-frequency and high-temperature conditions is solved, and a high-entropy alloy soft magnetic composite material with high-frequency and low loss and good heat resistance and heat dissipation performance is achieved.

CN119626700APending Publication Date: 2025-03-14HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411757494.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing metal soft magnetic composite materials are difficult to meet the requirements of low magnetic loss and good temperature stability under high frequency and high temperature conditions, resulting in limited application in electronic devices.

Method used

A high-entropy alloy powder with a negative temperature coefficient is used to form a high-entropy alloy soft magnetic composite material to satisfy the general formula FeaCobNicCrdAle, and is synergistically coated by the inorganic insulating layer and the organic insulating layer to form a high-entropy alloy soft magnetic composite material.

Benefits of technology

It achieves high-frequency, low-loss and good heat-resistant and heat dissipation performance, and can meet the needs of electronic and electrical appliances under high-frequency and high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166705910000201
    Figure BDA0005166705910000201
  • Figure BDA0005166705910000211
    Figure BDA0005166705910000211
  • Figure BDA0005166705910000212
    Figure BDA0005166705910000212
Patent Text Reader

Abstract

The invention relates to a high-entropy alloy soft magnetic composite material and a preparation method and application thereof. The high-entropy alloy soft magnetic composite material comprises high-entropy alloy powder, an inorganic insulating layer and an organic insulating layer, wherein the surface of the high-entropy alloy powder is sequentially coated with the inorganic insulating layer and the organic insulating layer; the composition of the high-entropy alloy powder meets the general formula of FeaCobNicCrdAle, a, b, c, d and e represent the atomic percent of corresponding alloy elements respectively, 20 < = a = b = c < = 25, 10 < = d < = 15, 15 < = e < = 25, and a + b + c + d + e = 100. The high-entropy alloy powder with the negative temperature coefficient is adopted as the magnetic powder, the resistivity of the alloy is increased along with temperature rise, so that eddy current loss can be inhibited, and after the inorganic insulating layer and the organic insulating layer are cooperatively matched, the high-entropy alloy soft magnetic composite material has high frequency, low loss and good heat resistance and heat dissipation performance; the requirements in the field of high-frequency and high-temperature electronics can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic materials, and particularly to a high-entropy alloy soft magnetic composite material, a preparation method thereof, and an application thereof. Background Art

[0002] Metal soft magnetic composite materials are widely used in fields such as photovoltaic power generation, variable-frequency air conditioners, new energy vehicles and charging piles, data centers, energy storage, and consumer electronics due to their characteristics such as high saturation magnetic flux density and wide operating frequency range. Metal soft magnetic composite materials are usually composed of soft magnetic particles with an insulating coating structure. Among them, the presence of the insulating coating layer has a key impact on the properties of metal soft magnetic composite materials such as saturation magnetization intensity, coercive force, and resistivity. At present, commonly used insulating coating layers with high resistivity and uniform coating, such as phosphate / silicone resin composite coating and SiO2 / epoxy resin composite coating, have been studied by many scholars and achieved the goal of high resistance and low loss. However, in the face of the development trend of thin, light, small, integrated, and intelligent electronic devices and the working environment of high current and high frequency, it is not only required that the metal soft magnetic composite material has low loss performance at high frequencies, but also has high requirements for its temperature stability.

[0003] At present, when commercially available FeSiAl and FeSi composite soft magnetic materials are used in the medium and high frequency bands, the eddy current loss is large, and thus the problem of heat generation inevitably occurs. As the material temperature increases, its resistivity further decreases, which in turn leads to an increase in eddy current loss, thus forming a vicious cycle, making it impossible to be applied in high-frequency or high-temperature fields. For another example, although amorphous nanocrystalline materials have low loss performance, they are not suitable for high-temperature scenarios due to their unique structure. Therefore, it is of great significance to develop a metal soft magnetic composite material with high-frequency low-loss performance and high-temperature stability to solve the application problems of electronic devices in high-frequency and high-temperature scenarios.

[0004] CN116445790A discloses a soft magnetic high-entropy alloy, a soft magnetic composite material prepared therefrom, and a preparation method. The composition of the soft magnetic high-entropy alloy satisfies the general formula Al a Co b Fe c Cr d M e , where M is selected from one of Cu, Si, or C; and a, b, c, d, and e respectively represent the atomic percentages of the corresponding alloy elements, 15≤a≤20, 40≤b≤50, 20≤c≤25, 10≤d + e≤20, 0 < d / e≤10, a + b + c + d + e = 100. The soft magnetic high-entropy alloy has high saturation magnetization intensity, low coercive force, and good temperature stability. However, the magnetic permeability of the magnetic powder core prepared therefrom is low and the loss is high, making it difficult to be applied in actual magnetic components.

[0005] CN116013631A discloses a FeSiAl composite soft magnetic powder core and its preparation method. This method uses nano-aluminum to thermally generate an aluminum oxide coating. The composite soft magnetic material has a structure of a 5-20nm aluminum oxide coating, a 5-50nm thick magnetic metal layer, and a 50-200nm thick silicon dioxide layer. Although the powder core has high magnetic permeability and low loss performance, the coating material has low thermal conductivity, which makes it difficult to achieve good thermal conductivity and heat dissipation. In addition, the resistivity of the FeSiAl alloy decreases with increasing temperature, making it unsuitable for high-frequency and high-temperature applications.

[0006] It can be seen that the current existing technologies cannot simultaneously meet the requirements of composite materials having low magnetic loss and good temperature stability under high frequency and high temperature. For high temperature and high frequency service environments, both magnetic metal powder and insulating coating layers must have high temperature stability and high efficiency.

[0007] Therefore, how to provide metal soft magnetic composite materials that have low loss and good heat resistance and heat dissipation performance under high temperature and high frequency has become an urgent problem to be solved, so as to meet the future needs of the high-frequency and high-temperature electronic and electrical fields. Summary of the Invention

[0008] In order to solve the above technical problems, the present invention provides a high entropy alloy soft magnetic composite material and its preparation method and application. The present invention adopts a negative temperature coefficient and a composition that satisfies the general formula Fe a Co b Ni c Cr d Al e High-entropy alloy powder is used as magnetic powder. As the temperature increases, the resistivity of the alloy increases, thereby suppressing eddy current loss. After being coated with an inorganic insulating layer and an organic insulating layer, the two are coordinated to obtain a high-entropy alloy soft magnetic composite material with high frequency, low loss and good heat resistance and heat dissipation performance, which can meet the needs of the electronic and electrical fields under high frequency and high temperature conditions.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a high entropy alloy soft magnetic composite material, the high entropy alloy soft magnetic composite material comprising a high entropy alloy powder, and an inorganic insulating layer and an organic insulating layer sequentially coated on the surface of the high entropy alloy powder;

[0011] The composition of the high entropy alloy powder satisfies the general formula Fe a Co b Ni c Cr d Al e, wherein a, b, c, d and e represent the atomic percentages of the corresponding alloying elements, respectively, 20≤a=b=c≤25, for example, a may be 20, 21, 22, 23, 24 or 25, etc., b may be 20, 21, 22, 23, 24 or 25, etc., c may be 20, 21, 22, 23, 24 or 25, etc., 10≤d≤15, for example, d may be 10, 11, 12, 13, 14 or 15, etc., 15≤e≤25, for example, e may be 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or 25, etc., and a+b+c+d+e=100.

[0012] It should be noted that the inorganic insulating layer and the organic insulating layer of the high entropy alloy soft magnetic composite material are two-layer structures that are independently coated. The inorganic insulating layer is coated on the surface of the high entropy alloy powder, and the organic insulating layer is coated on the surface of the inorganic insulating layer.

[0013] The magnetic powder used in the present invention is a composition satisfying the general formula Fe a Co b Ni c Cr d Al e High entropy alloy powder, Fe a Co b Ni c Cr d Al e The electrons in the high entropy alloy powder will generate greater scattering and resistance under the lattice vibration intensified by the temperature increase, and thus have a negative temperature coefficient, that is, as the temperature increases, the resistivity of the alloy will gradually increase, thereby better suppressing eddy current loss; further, the present invention uses an inorganic insulating layer and an organic insulating layer to coat the surface of the high entropy alloy powder, wherein the coating of the inorganic insulating layer can effectively improve the resistivity, heat resistance and thermal conductivity of the metal magnetic powder core; the coating of the organic insulating layer can reduce the loss, and on the basis of containing the inorganic insulating layer, further promote the improvement of heat resistance, and the organic insulating layer material can also play the role of a binder, omitting the additional addition of the binder. After the two are coordinated, they are combined to form a composition that satisfies the general formula Fe a Co b Ni c Cr d Al e The high entropy alloy powder is used to obtain a high entropy alloy soft magnetic composite material with low loss at high frequency and good heat resistance and heat dissipation performance, which can meet the needs of the electronic and electrical fields under high frequency and high temperature conditions.

[0014] As a preferred technical solution of the present invention, in the high entropy alloy soft magnetic composite material, the inorganic insulating layer material has a one-dimensional structure.

[0015] Preferably, the inorganic insulating layer material includes aluminum nitride.

[0016] Preferably, the inorganic insulating layer and the organic insulating layer are coupled and bonded via a coupling agent.

[0017] Preferably, in the high entropy alloy soft magnetic composite material, the organic insulating layer material includes silicone resin.

[0018] Preferably, the organic silicone resin includes silicon-containing aromatic acetylene resin or methylphenyl silicone resin.

[0019] Preferably, the average particle size D50 of the high entropy alloy powder is 15 μm-75 μm, for example, 15 μm, 25 μm, 35 μm, 45 μm, 55 μm, 65 μm or 75 μm.

[0020] In the present invention, the particle size of the high-entropy alloy powder affects the performance of the high-entropy alloy soft magnetic composite. Adjusting the average particle size D50 of the high-entropy alloy powder to 15μm-75μm ensures that the resulting composite material has lower losses and higher magnetic permeability. If the particle size is too small, hysteresis losses are difficult to reduce, and the high cost of fine powder makes industrialization unfavorable. If the particle size is too large, it is difficult to reduce eddy current losses within the particles, resulting in excessively high core losses at high frequencies.

[0021] In a second aspect, the present invention further provides a method for preparing the high entropy alloy soft magnetic composite material according to the first aspect, the preparation method comprising the following steps:

[0022] (1) performing a first mixing of high entropy alloy powder and inorganic insulating layer material to obtain a first coated powder;

[0023] (2) a second mixing of a solution containing an organic insulating layer material and the first coated powder, granulating the mixture to obtain a second coated powder, and pressing and annealing the mixture to obtain a high entropy alloy soft magnetic composite material;

[0024] The composition of the high entropy alloy powder satisfies the general formula Fe a Co b Ni c Cr d Al e , where a, b, c, d, and e represent the atomic percentages of the corresponding alloying elements, 20≤a=b=c≤25, 10≤d≤15, 15≤e≤25, and a+b+c+d+e=100.

[0025] As a preferred technical solution of the present invention, the method for preparing the high entropy alloy powder in step (1) comprises:

[0026] Fe powder, Co powder, Ni powder, Cr powder and Al powder are mixed and then dry-milled to obtain the high entropy alloy powder.

[0027] It should be noted that the addition amounts of the Fe powder, the Co powder, the Ni powder, the Cr powder and the Al powder in the present invention are determined according to the general formula of the high entropy alloy powder: a Co b Ni c Cr d Al e Adaptive selection and adjustment are performed, wherein a, b, c, d and e represent the atomic percentages of the corresponding alloying elements, 20≤a=b=c≤25, 10≤d≤15, 15≤e≤25, and a+b+c+d+e=100.

[0028] Preferably, the purity of the Fe powder, the Co powder, the Ni powder, the Cr powder and the Al powder is independently ≥99.8%, such as 99.8%, 99.85% or 99.9%.

[0029] Preferably, the dry ball milling is performed under an inert atmosphere.

[0030] Preferably, the inert atmosphere includes an argon atmosphere or a helium atmosphere.

[0031] Preferably, the rotational speed of the dry ball mill is 100 rpm-400 rpm, for example, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm or 400 rpm.

[0032] Preferably, the rotation speed of the dry ball mill is 200 rpm-600 rpm, for example, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm or 600 rpm, etc.

[0033] Preferably, the dry ball milling time is 12 h to 24 h, for example, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h or 24 h.

[0034] As a preferred technical solution of the present invention, based on the mass of the high entropy alloy powder, the mass of the inorganic insulating layer material in step (1) is 1wt%-5wt%, for example, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc.

[0035] In the present invention, the inorganic insulating layer material is adjusted to a mass between 1wt% and 5wt%, enabling different coating thicknesses to be achieved, thereby regulating the high-entropy alloy soft magnetic composite material to achieve superior high-frequency, low-loss, and good heat-resistance and heat-dissipation properties. Excessive content and excessively thick coating layers significantly reduce the magnetic permeability of the high-entropy alloy soft magnetic composite material while increasing hysteresis losses. Excessive content and excessively thin coating layers can prevent effective insulation and insufficient thermal conductivity, thereby affecting the loss and heat-dissipation properties of the high-entropy alloy soft magnetic composite material.

[0036] Preferably, the method of first mixing the high entropy alloy powder and the inorganic insulating layer material in step (1) comprises:

[0037] After mixing the high entropy alloy powder and the inorganic insulating layer material, a solvent is added and wet ball milling is performed.

[0038] Preferably, the solvent comprises anhydrous ethanol.

[0039] Preferably, the wet ball milling time is 2 h to 6 h, for example, 2 h, 3 h, 4 h, 5 h or 6 h.

[0040] Preferably, the wet ball mill has a rotational speed of 50 rpm to 80 rpm, such as 50 rpm, 60 rpm, 70 rpm or 80 rpm.

[0041] Preferably, the rotation speed of the wet ball mill is 100 rpm-200 rpm, such as 100 rpm, 120 rpm, 140 rpm, 160 rpm, 180 rpm or 200 rpm.

[0042] It should be noted that the present invention does not impose any specific limitation on the amount of solvent added in wet ball milling, as long as it can cover the powder. The amount can be adaptively selected and adjusted according to actual conditions.

[0043] As a preferred technical solution of the present invention, after the wet ball milling, the method further includes subjecting the wet ball milled powder to a first drying step, ultrasonically mixing the powder with a solution containing a silane coupling agent, and then subjecting the powder to a second drying step to obtain a first coated powder.

[0044] Preferably, the first drying temperature is 60°C-150°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0045] Preferably, the first drying time is 30 min-60 min, such as 30 min, 40 min, 50 min or 60 min.

[0046] Preferably, in the solution containing a silane coupling agent, the silane coupling agent includes any one of vinyl silane, alkyl silane or amino silane, or a combination of at least two of them.

[0047] Preferably, the vinyl silane includes any one of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl triisopropoxysilane or vinyl triacetoxysilane, or a combination of at least two thereof.

[0048] Preferably, the alkylsilane includes any one of methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, propyltrimethoxysilane or propyltriethoxysilane, or a combination of at least two thereof.

[0049] Preferably, the aminosilane includes any one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane or γ-aminopropylmethyldimethoxysilane, or a combination of at least two thereof.

[0050] In the present invention, the first coating powder is mixed with a solution containing a silane coupling agent. The addition of the silane coupling agent can increase the coupling effect between the inorganic insulating layer and the organic insulating layer, thereby facilitating better bonding between the insulating layers.

[0051] Preferably, based on the mass of the high entropy alloy powder, the mass of the silane coupling agent is 0.5wt%-2wt%, for example, 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt%, 1.8wt% or 2wt%.

[0052] Preferably, in the solution containing the silane coupling agent, the solvent includes any one of anhydrous ethanol, methanol, ethylene glycol or acetone, or a combination of at least two of them.

[0053] It should be noted that the present invention does not impose any specific requirements or restrictions on the amount of solvent added to the solution containing the silane coupling agent. The amount of solvent added is based on the standard of being able to immerse the silane coupling agent material and achieve uniform coating, and can be adjusted and selected according to actual needs.

[0054] Preferably, the ultrasonic mixing process also includes stirring.

[0055] Preferably, the ultrasonic mixing time is ≥10 min, for example, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 25 min or 30 min, etc.

[0056] Preferably, the frequency of the ultrasonic mixing is 20 kHz-40 kHz, such as 20 kHz, 25 kHz, 30 kHz, 35 kHz or 40 kHz.

[0057] Preferably, the second drying temperature is 60°C-150°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0058] Preferably, the second drying time is 30 min-60 min, such as 30 min, 40 min, 50 min or 60 min.

[0059] As a preferred technical solution of the present invention, based on the mass of the high entropy alloy powder, the mass of the organic insulating layer material in the solution containing the organic insulating layer material in step (2) is 0.8wt%-4wt%, for example, 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt% or 4wt%, etc.

[0060] In the present invention, the organic insulating layer material serves as both an insulating coating and a binder. By adjusting the mass of the organic insulating layer material to between 0.8wt% and 4wt%, varying coating thicknesses can be achieved, thereby enabling the high-entropy alloy soft magnetic composite to exhibit superior high-frequency, low-loss, and heat-resistant properties. Excessive organic insulating layer thickness significantly reduces the permeability and increases hysteresis losses of the composite. Excessive organic insulating layer thickness significantly reduces the permeability and increases hysteresis losses of the composite. Excessive organic insulating layer thickness significantly reduces the permeability and increases hysteresis losses of the composite. Excessive organic insulating layer thickness, however, renders the coating layer ineffective, preventing effective insulating and bonding properties.

[0061] Preferably, in the solution containing the organic insulating layer material in step (2), the solvent includes any one of acetone, toluene or xylene, or a combination of at least two of them.

[0062] It should be noted that the present invention does not impose any specific requirements or restrictions on the amount of solvent added to the solution containing the organic insulating layer material. The standard is that the organic insulating layer material can be immersed and uniform coating can be achieved, and the amount can be adjusted and selected according to actual needs.

[0063] Preferably, the second mixing in step (2) includes ultrasonic treatment, and the ultrasonic treatment also includes stirring.

[0064] Preferably, the ultrasonic treatment time is ≥10 min, for example, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 25 min or 30 min, etc.

[0065] Preferably, the frequency of the ultrasonic treatment is 20 kHz-40 kHz, such as 20 kHz, 25 kHz, 30 kHz, 35 kHz or 40 kHz.

[0066] Preferably, in the granulation process of step (2), the mesh size of the sieve used for sieving is 50-100 mesh, for example, 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh or 100 mesh.

[0067] Preferably, after the granulation in step (2), the process further comprises subjecting the granulated powder to a third drying step.

[0068] It should be noted that the present invention does not impose any specific requirements or restrictions on the temperature and time of the third drying after granulation. As long as the powder can be completely dried, it is applicable to the present invention. For example, the drying temperature can be 60° C. and the drying time can be 12 hours.

[0069] As a preferred technical solution of the present invention, before the pressing and forming in step (2), the second coated powder is further mixed with a release agent for a third time.

[0070] Preferably, the release agent comprises zinc stearate or magnesium stearate.

[0071] Preferably, based on the mass of the high entropy alloy powder, the mass of the release agent in step (3) is 0.1wt%-0.3wt%, such as 0.1wt%, 0.2wt% or 0.3wt%.

[0072] Preferably, the pressure of the press molding in step (2) is 1500 MPa-2000 MPa, for example, 1500 MPa, 1600 MPa, 1700 MPa, 1800 MPa, 1900 MPa or 2000 MPa.

[0073] Preferably, the annealing temperature in step (2) is 700°C-900°C, for example, 700°C, 750°C, 800°C, 850°C or 900°C.

[0074] Preferably, the annealing time in step (2) is 45 min-120 min, for example, 45 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.

[0075] Preferably, the annealing in step (2) is performed under a protective atmosphere.

[0076] Preferably, the protective atmosphere includes a nitrogen atmosphere or an argon atmosphere.

[0077] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0078] (1) Fe powder, Co powder, Ni powder, Cr powder and Al powder with a purity of ≥99.8% are mixed, and dry ball milled at a speed of 200 rpm to 600 rpm for 12 h to 24 h in an inert atmosphere to obtain a high entropy alloy powder with an average particle size D50 of 15 μm to 75 μm, wherein the composition of the high entropy alloy powder satisfies the general formula Fe a Co b Ni c Cr d Al e , where a, b, c, d, and e represent the atomic percentages of the corresponding alloying elements, 20≤a=b=c≤25, 10≤d≤15, 15≤e≤25, and a+b+c+d+e=100;

[0079] After mixing the high entropy alloy powder and the inorganic insulating layer material, a solvent is added, and the powder is wet-milled at a rotation speed of 100 rpm to 200 rpm for 2 h to 6 h to perform a first mixing. The powder after the wet ball milling is dried at 60° C. to 150° C. for 30 min to 60 min. After the first drying, the powder is ultrasonically mixed with a solution containing a silane coupling agent at a frequency of 20 kHz to 40 kHz for ≥ 10 min. The ultrasonic mixing process also includes stirring. The powder after the ultrasonic mixing is dried at 60° C. to 150° C. for 30 min to 60 min. After the second drying, a first coated powder is obtained;

[0080] Based on the mass of the high entropy alloy powder, the mass of the inorganic insulating layer material is 1wt%-5wt%;

[0081] (2) ultrasonically treating the solution containing the organic insulating layer material and the first coating powder at a frequency of 20kHz-40kHz for ≥10min, wherein the ultrasonic treatment process also includes stirring, performing a second mixing, granulating and screening the sieve with a mesh size of 50-100 mesh, and performing a third drying on the granulated powder to obtain a second coating powder;

[0082] Based on the mass of the high entropy alloy powder, the mass of the organic insulating layer material in the solution containing the organic insulating layer material is 0.8wt%-4wt%;

[0083] After a third mixing of the release agent and the second coated powder, the mixture is pressed under a pressure of 1500 MPa to 2000 MPa, and annealed at 700° C. to 900° C. for 45 min to 120 min under a protective atmosphere to obtain a high entropy alloy soft magnetic composite material;

[0084] Based on the mass of the high entropy alloy powder, the mass of the release agent is 0.1wt%-0.3wt%.

[0085] In a third aspect, the present invention also provides an application of a high entropy alloy soft magnetic composite material, wherein the high entropy alloy soft magnetic composite material described in the first aspect, or the high entropy alloy soft magnetic composite material prepared by the preparation method described in the second aspect, is applied to magnetic electronic components.

[0086] Compared with the prior art, the present invention has at least the following beneficial effects:

[0087] 1) The high entropy alloy soft magnetic composite material of the present invention adopts a negative temperature coefficient and a composition satisfying the general formula Fe a Co b Ni c Cr d Al e The high entropy alloy powder is used as a soft magnetic powder. As the temperature increases, the resistivity of the alloy will gradually increase, thereby suppressing eddy current loss.

[0088] 2) The high-entropy alloy soft magnetic composite material of the present invention is coated with an inorganic insulating layer and an organic insulating layer, wherein the coating of the inorganic insulating layer can effectively improve the resistivity, heat resistance and thermal conductivity of the metal magnetic powder core. The use of an inorganic insulating layer material with a one-dimensional structure can construct more heat conduction channels in the insulating layer, which is beneficial to heat dissipation; the coating of the organic insulating layer can reduce the loss and, on the basis of containing the inorganic insulating layer, further promote the improvement of heat resistance, and the organic insulating layer material can also act as a binder.

[0089] 3) The high-entropy alloy soft magnetic composite material of the present invention is coated with an inorganic insulating layer and an organic insulating layer, both of which have high electrical resistance and can also effectively reduce the loss of the magnetic core at high frequencies. DETAILED DESCRIPTION

[0090] For the convenience of understanding the present invention, the present invention is given below with examples. It should be understood by those skilled in the art that the examples are only for the purpose of helping to understand the present invention and should not be regarded as specific limitations of the present invention.

[0091] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0092] Example 1

[0093] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof, wherein the high entropy alloy soft magnetic composite material comprises a high entropy alloy powder, and a one-dimensional aluminum nitride insulating layer and a silicon-containing aromatic acetylene resin insulating layer sequentially coated on the surface of the high entropy alloy powder, wherein the composition of the high entropy alloy powder is Fea Co b Ni c Cr d Al e , wherein a=b=c=22, d=12, e=22, and the average particle size D50 of the high entropy alloy powder is 30 μm;

[0094] The preparation method comprises the following steps:

[0095] (1) Fe powder, Co powder, Ni powder, Cr powder, and Al powder with a purity of 99.8% were mixed and placed in a ball mill filled with argon gas. The ball-to-material mass ratio was 20:1. The mixture was ball milled at a speed of 400 rpm for 16 h to obtain a high entropy alloy powder.

[0096] After mixing high entropy alloy powder and 2 wt% (based on the mass of the high entropy alloy powder) of one-dimensional aluminum nitride powder, anhydrous ethanol was added, the ball-to-material mass ratio was 20:1, and wet ball milling was carried out at a speed of 150 rpm for 6 h. After drying at 80° C. for 45 min, an anhydrous ethanol solution containing 0.5 wt% (based on the mass of the high entropy alloy powder) of γ-aminopropyltriethoxysilane was added, and the mixture was stirred and ultrasonically mixed for 10 min at an ultrasonic frequency of 30 kHz. After drying at 80° C. for 45 min, a first coated powder was obtained;

[0097] (2) 1.4 wt% (based on the mass of the high entropy alloy powder) of silicon-containing aromatic acetylene resin was dissolved in acetone to obtain a solution containing silicon-containing aromatic acetylene resin, which was then mixed with the first coated powder and stirred and ultrasonically treated for 10 min at an ultrasonic frequency of 30 kHz. The powder was granulated and sieved through a 60-mesh sieve, and dried at 60° C. for 12 h to obtain a second coated powder.

[0098] 0.2 wt% (based on the mass of the high entropy alloy powder) of zinc stearate was added to the second coated powder, mixed and pressed under a pressure of 1800 MPa to obtain a magnetic ring green body with OD = 12.75 mm and ID = 7.60 mm. The green body was annealed at 720 ° C for 60 min in a nitrogen atmosphere to obtain a high entropy alloy soft magnetic composite material.

[0099] Example 2

[0100] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof, wherein the high entropy alloy soft magnetic composite material comprises a high entropy alloy powder, and a one-dimensional aluminum nitride insulating layer and a silicon-containing aromatic acetylene resin insulating layer sequentially coated on the surface of the high entropy alloy powder, wherein the composition of the high entropy alloy powder is Fe a Co b Ni c Cr d Ale , wherein a=b=c=22, d=12, e=22, and the average particle size D50 of the high entropy alloy powder is 30 μm;

[0101] The preparation method comprises the following steps:

[0102] (1) Fe powder, Co powder, Ni powder, Cr powder, and Al powder with a purity of 99.8% were mixed and placed in a ball mill filled with argon gas. The ball-to-material mass ratio was 20:1. The mixture was ball milled at a speed of 200 rpm for 12 h to obtain a high entropy alloy powder.

[0103] After mixing high entropy alloy powder and 1.5wt% (based on the mass of the high entropy alloy powder) of one-dimensional aluminum nitride powder, anhydrous ethanol was added, the ball-to-material mass ratio was 20:1, and wet ball milling was carried out at a speed of 100 rpm for 2 hours. After drying at 60°C for 60 minutes, an anhydrous ethanol solution containing 1.5wt% (based on the mass of the high entropy alloy powder) of vinyltriethoxysilane was added, stirred and ultrasonically mixed for 15 minutes at an ultrasonic frequency of 40kHz, and dried at 60°C for 60 minutes to obtain a first coated powder;

[0104] (2) 0.8 wt% (based on the mass of the high entropy alloy powder) of silicon-containing aromatic acetylene resin was dissolved in acetone to obtain a solution containing silicon-containing aromatic acetylene resin, which was then mixed with the first coated powder and stirred and ultrasonically treated for 15 min at an ultrasonic frequency of 40 kHz. The powder was granulated and sieved through an 80-mesh sieve, and dried at 60° C. for 12 h to obtain a second coated powder.

[0105] 0.1 wt% (based on the mass of the high entropy alloy powder) of zinc stearate was added to the second coated powder, mixed and pressed under a pressure of 1500 MPa to obtain a magnetic ring green body with OD = 12.75 mm and ID = 7.60 mm. The green body was annealed at 700 ° C for 120 min in a nitrogen atmosphere to obtain a high entropy alloy soft magnetic composite material.

[0106] Example 3

[0107] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof, wherein the high entropy alloy soft magnetic composite material comprises a high entropy alloy powder, and a one-dimensional aluminum nitride insulating layer and a methylphenyl silicone resin insulating layer sequentially coated on the surface of the high entropy alloy powder, wherein the composition of the high entropy alloy powder is Fe a Co b Ni c Cr d Al e , wherein a=b=c=22, d=12, e=22, and the average particle size D50 of the high entropy alloy powder is 30 μm;

[0108] The preparation method comprises the following steps:

[0109] (1) Fe powder, Co powder, Ni powder, Cr powder, and Al powder with a purity of 99.8% were mixed and placed in a ball mill filled with argon gas. The ball-to-material mass ratio was 20:1. The mixture was ball milled at a speed of 600 rpm for 20 h to obtain a high entropy alloy powder.

[0110] After mixing high entropy alloy powder and 2.5wt% (based on the mass of the high entropy alloy powder) of one-dimensional aluminum nitride powder, anhydrous ethanol was added, the ball-to-material mass ratio was 20:1, and wet ball milling was carried out at a speed of 200 rpm for 4 hours. After drying at 150°C for 30 minutes, an anhydrous ethanol solution containing 2wt% (based on the mass of the high entropy alloy powder) of methyltrimethoxysilane was added, stirred and ultrasonically mixed for 20 minutes at an ultrasonic frequency of 20kHz, and dried at 150°C for 30 minutes to obtain a first coated powder;

[0111] (2) dissolving 4 wt% (based on the mass of the high entropy alloy powder) of methylphenyl silicone resin in acetone to obtain a solution containing methylphenyl silicone resin, mixing the solution with the first coated powder and stirring the solution, and ultrasonically treating the solution for 20 min at an ultrasonic frequency of 20 kHz. The solution was granulated and sieved through a 100-mesh sieve, and dried at 60° C. for 12 h to obtain a second coated powder.

[0112] 0.3 wt% (based on the mass of the high entropy alloy powder) of zinc stearate was added to the second coated powder, mixed and pressed under a pressure of 2000 MPa to obtain a magnetic ring green body with OD = 12.75 mm and ID = 7.60 mm. The green body was annealed at 900 ° C for 45 min in a nitrogen atmosphere to obtain a high entropy alloy soft magnetic composite material.

[0113] Example 4

[0114] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high entropy alloy soft magnetic composite material and embodiment 1 is that the composition of the high entropy alloy powder is Fe a Co b Ni c Cr d Al e , wherein a=b=c=22, d=10, e=24, and the particle size, coating layer structure and material of the high entropy alloy powder are consistent with those in Example 1;

[0115] The difference between the preparation method and Example 1 is that in step (1), Fe powder, Co powder, Ni powder, Cr powder and Al powder are mixed according to the composition of the above-mentioned high entropy alloy powder, and the remaining preparation methods and parameters are consistent with Example 1.

[0116] Example 5

[0117] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high entropy alloy soft magnetic composite material and embodiment 1 is that the composition of the high entropy alloy powder is Fe a Co b Ni c Cr d Al e , wherein a=b=c=22, d=11, e=23, and the particle size, coating layer structure and material of the high entropy alloy powder are consistent with those in Example 1;

[0118] The difference between the preparation method and Example 1 is that in step (1), Fe powder, Co powder, Ni powder, Cr powder and Al powder are mixed according to the composition of the above-mentioned high entropy alloy powder, and the remaining preparation methods and parameters are consistent with Example 1.

[0119] Example 6

[0120] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high entropy alloy soft magnetic composite material and embodiment 1 is that the composition of the high entropy alloy powder is Fe a Co b Ni c Cr d Al e , wherein a=b=c=22, d=13, e=21, and the particle size, coating layer structure and material of the high entropy alloy powder are consistent with those in Example 1;

[0121] The difference between the preparation method and Example 1 is that in step (1), Fe powder, Co powder, Ni powder, Cr powder and Al powder are mixed according to the composition of the above-mentioned high entropy alloy powder, and the remaining preparation methods and parameters are consistent with Example 1.

[0122] Example 7

[0123] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high entropy alloy soft magnetic composite material and embodiment 1 is that the composition of the high entropy alloy powder is Fe a Co b Ni c Cr d Al e, wherein a=b=c=22, d=14, e=20, and the particle size, coating layer structure and material of the high entropy alloy powder are consistent with those in Example 1;

[0124] The difference between the preparation method and Example 1 is that in step (1), Fe powder, Co powder, Ni powder, Cr powder and Al powder are mixed according to the composition of the above-mentioned high entropy alloy powder, and the remaining preparation methods and parameters are consistent with Example 1.

[0125] Example 8

[0126] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high entropy alloy soft magnetic composite material and embodiment 1 is that the composition of the high entropy alloy powder is Fe a Co b Ni c Cr d Al e , wherein a=b=c=22, d=15, e=19, and the particle size, coating layer structure and material of the high entropy alloy powder are consistent with those in Example 1;

[0127] The difference between the preparation method and Example 1 is that in step (1), Fe powder, Co powder, Ni powder, Cr powder and Al powder are mixed according to the composition of the above-mentioned high entropy alloy powder, and the remaining preparation methods and parameters are consistent with Example 1.

[0128] Example 9

[0129] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high entropy alloy soft magnetic composite material and embodiment 1 is that the composition of the high entropy alloy powder is Fe a Co b Ni c Cr d Al e , wherein a=b=c=20, d=15, e=25, and the particle size, coating layer structure and material of the high entropy alloy powder are consistent with those in Example 1;

[0130] The difference between the preparation method and Example 1 is that in step (1), Fe powder, Co powder, Ni powder, Cr powder and Al powder are mixed according to the composition of the above-mentioned high entropy alloy powder, and the remaining preparation methods and parameters are consistent with Example 1.

[0131] Example 10

[0132] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high entropy alloy soft magnetic composite material and embodiment 1 is that the composition of the high entropy alloy powder is Fe a Co b Nic Cr d Al e , wherein a=b=c=25, d=10, e=15, and the particle size, coating layer structure and material of the high entropy alloy powder are consistent with those in Example 1;

[0133] The difference between the preparation method and Example 1 is that in step (1), Fe powder, Co powder, Ni powder, Cr powder and Al powder are mixed according to the composition of the above-mentioned high entropy alloy powder, and the remaining preparation methods and parameters are consistent with Example 1.

[0134] Example 11

[0135] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The structure and composition of the high entropy alloy soft magnetic composite material are consistent with those in Example 1.

[0136] The difference between the preparation method and Example 1 is that the mass of the one-dimensional aluminum nitride powder in step (1) is 1 wt %, and the other preparation methods and parameters are consistent with Example 1.

[0137] Example 12

[0138] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The structure and composition of the high entropy alloy soft magnetic composite material are consistent with those in Example 1.

[0139] The difference between the preparation method and Example 1 is that the mass of the one-dimensional aluminum nitride powder in step (1) is 3 wt %, and the other preparation methods and parameters are consistent with Example 1.

[0140] Example 13

[0141] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The structure and composition of the high entropy alloy soft magnetic composite material are consistent with those in Example 1.

[0142] The difference between the preparation method and Example 1 is that the mass of the one-dimensional aluminum nitride powder in step (1) is 4 wt %, and the other preparation methods and parameters are consistent with Example 1.

[0143] Example 14

[0144] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The structure and composition of the high entropy alloy soft magnetic composite material are consistent with those in Example 1.

[0145] The difference between the preparation method and Example 1 is that the mass of the one-dimensional aluminum nitride powder in step (1) is 5 wt %, and the other preparation methods and parameters are consistent with Example 1.

[0146] Example 15

[0147] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The structure and composition of the high entropy alloy soft magnetic composite material are consistent with those in Example 1.

[0148] The difference between the preparation method and Example 1 is that the mass of the one-dimensional aluminum nitride powder in step (1) is 0.5 wt %, and the other preparation methods and parameters are consistent with Example 1.

[0149] Example 16

[0150] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The structure and composition of the high entropy alloy soft magnetic composite material are consistent with those in Example 1.

[0151] The difference between the preparation method and Example 1 is that the mass of the one-dimensional aluminum nitride powder in step (1) is 6 wt %, and the other preparation methods and parameters are consistent with Example 1.

[0152] Example 17

[0153] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The structure and composition of the high entropy alloy soft magnetic composite material are consistent with those in Example 1.

[0154] The difference between the preparation method and Example 1 is that the mass of the silicon-containing aromatic acetylene resin in step (2) is 0.4 wt %, and the other preparation methods and parameters are consistent with Example 1.

[0155] Example 18

[0156] This embodiment provides a high entropy alloy soft magnetic composite material and a preparation method thereof. The structure and composition of the high entropy alloy soft magnetic composite material are consistent with those in Example 1.

[0157] The difference between the preparation method and Example 1 is that the mass of the silicon-containing aromatic acetylene resin in step (2) is 4.5 wt %, and the other preparation methods and parameters are consistent with those in Example 1.

[0158] Example 19

[0159] This embodiment provides a high-entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high-entropy alloy soft magnetic composite material and Example 1 is that the average particle size D50 of the high-entropy alloy powder is 10 μm, and the rest of the structure and composition are consistent with Example 1;

[0160] The difference between the preparation method and Example 1 is that the average particle size D50 of the high entropy alloy powder in step (1) is 10 μm, and the other preparation methods and parameters are consistent with Example 1.

[0161] Example 20

[0162] This embodiment provides a high-entropy alloy soft magnetic composite material and a preparation method thereof. The difference between the high-entropy alloy soft magnetic composite material and Example 1 is that the average particle size D50 of the high-entropy alloy powder is 80 μm, and the rest of the structure and composition are consistent with Example 1;

[0163] The difference between the preparation method and Example 1 is that the average particle size D50 of the high entropy alloy powder in step (1) is 80 μm, and the other preparation methods and parameters are consistent with Example 1.

[0164] Comparative Example 1

[0165] This comparative example provides an alloy soft magnetic composite material and a preparation method thereof. The alloy soft magnetic composite material differs from Example 1 in that the alloy powder is commercially available FeSiAl, the average particle size D50 is 30 μm, and the coating layer structure and material are consistent with Example 1;

[0166] The difference between the preparation method and Example 1 is that in step (1), the high entropy alloy powder is replaced by an equal amount of commercially available FeSiAl alloy powder, and the rest of the preparation method and parameters remain the same as in Example 1.

[0167] Comparative Example 2

[0168] This comparative example provides an alloy soft magnetic composite material and a preparation method thereof. The alloy soft magnetic composite material differs from Example 1 in that the alloy powder is commercially available FeNi, the average particle size D50 is 30 μm, and the coating layer structure and material are consistent with Example 1;

[0169] The difference between the preparation method and Example 1 is that in step (1), the high entropy alloy powder is replaced by an equal amount of commercially available FeNi alloy powder, and the rest of the preparation method and parameters remain the same as in Example 1.

[0170] Comparative Example 3

[0171] This comparative example provides a high-entropy alloy soft magnetic composite material and a preparation method thereof. The high-entropy alloy soft magnetic composite material differs from Example 1 in that it does not contain a one-dimensional aluminum nitride insulating coating layer and only contains a silicon-containing aromatic acetylene resin coating layer. The remaining materials and composition are consistent with Example 1.

[0172] The difference between the preparation method and Example 1 is that the high entropy alloy powder is directly mixed with the solution containing the silicon-containing aromatic acetylene resin, and the subsequent mixing steps are performed. The remaining preparation methods and parameters are consistent with Example 1.

[0173] The high entropy alloy soft magnetic composite materials provided in Examples 1-10 and the alloy soft magnetic composite materials provided in Comparative Examples 1-2 were tested for saturation magnetization, resistivity (under 298k and 598k conditions) and loss (under 500kHz, 50mT, 298k and 500kHz, 50mT, 398k conditions). The specific data are shown in Table 1.

[0174] Table 1

[0175]

[0176]

[0177] The test results show that:

[0178] (1) It can be seen from Examples 1 to 10 that the present invention uses high entropy alloy powder with a negative temperature coefficient as the soft magnetic powder, and its composition satisfies the general formula Fe a Co b Ni c Cr d Al e , where a, b, c, d and e represent the atomic percentages of the corresponding alloy elements, 20≤a=b=c≤25, 10≤d≤15, 15≤e≤25, and a+b+c+d+e=100. Combined with the synergistic combination of the inorganic insulating layer and the organic insulating layer, high frequency, low loss and good heat resistance and heat dissipation performance can be achieved.

[0179] (2) It can be seen from Example 1 and Comparative Examples 1-2 that the present invention selects a negative temperature coefficient and a composition that satisfies the general formula Fe a Co b Ni c Cr d Al e When using high-entropy alloy powder, the resistivity of the alloy increases with increasing temperature, thereby suppressing eddy current loss; when using commercially available FeSiAl soft magnetic powder core, the resistivity decreases with increasing temperature, which will aggravate the eddy current loss of the composite material and cannot be used under high temperature and high frequency conditions; when using commercially available FeNi soft magnetic powder core, although the resistivity increases with increasing temperature, its resistivity is only 51.6μΩ*cm, which will also cause the soft magnetic composite material to have higher intra-particle eddy current loss at high frequency.

[0180] The core thermal conductivity, effective magnetic permeability and loss (under the conditions of 500kHz, 50mT, 298k) of the high entropy alloy soft magnetic composite materials provided in Example 1, Examples 11-20 and Comparative Example 3 were tested, and the specific data are shown in Table 2.

[0181] Table 2

[0182]

[0183]

[0184] The test results show that:

[0185] (1) It can be seen from Example 1, Example 11 to Example 14, and Comparative Example 3 that if one-dimensional aluminum nitride is not used for inorganic coating, the obtained high-entropy alloy soft magnetic composite material has higher core loss performance and lower core thermal conductivity. After one-dimensional aluminum nitride is used for coating, the core thermal conductivity gradually increases with the increase of the coating amount, and the loss is also around 452.5 mW / cm 3 -537.1mW / cm 3 The lower range indicates that the one-dimensional aluminum nitride inorganic coating layer can effectively play an insulating role, greatly reducing the eddy current loss between the magnetic powder particles and reducing the overall loss; on the other hand, one-dimensional aluminum nitride has a high thermal conductivity (about 320W / m·K) and its one-dimensional structure can build more heat conduction channels between the soft magnetic particles. Therefore, the thermal conductivity of the magnetic core increases with the increase of aluminum nitride content, greatly increasing the heat resistance and heat dissipation capacity of the magnetic powder core.

[0186] (2) It can be seen from Examples 15 to 16 that the present invention can control the high entropy alloy soft magnetic composite material to have better high frequency, low loss and good heat resistance and heat dissipation performance by further regulating the mass of the inorganic insulating layer material (one-dimensional aluminum nitride) to 1wt%-5wt%. If the content is too much, the inorganic coating layer is too thick. Although it can provide an effective insulating coating to reduce eddy current loss, the high content of non-magnetic phase mixed in the magnetic core will greatly reduce the effective magnetic permeability of the high entropy alloy soft magnetic composite material, while increasing the hysteresis loss, thereby increasing the overall loss; if the content is too little, the inorganic coating layer is too thin, and it cannot provide an effective insulation effect and establish a sufficient heat conduction path, which will also affect the overall loss performance and heat dissipation performance of the high entropy alloy soft magnetic composite material.

[0187] (3) It can be seen from Examples 17 to 18 that the present invention can control the high-entropy alloy soft magnetic composite material to have better high-frequency low loss and good heat resistance and heat dissipation performance by further regulating the mass of the organic insulating layer material to 0.8wt%-4wt%. If the content is too much, the organic coating layer is too thick, which means that the content of one-dimensional aluminum nitride is relatively reduced, and the excessively thick organic insulating layer will block the heat conduction channel between particles, thereby reducing the thermal conductivity of the magnetic core. Moreover, if the coating layer is too thick, it will reduce the effective magnetic permeability of the high-entropy alloy soft magnetic composite material and increase its hysteresis loss. If the content is too little, the organic coating layer is too thin, and it cannot provide an effective insulating coating effect and bonding effect.

[0188] (4) It can be seen from Examples 19 to 20 that the present invention can ensure that the prepared composite material has lower loss and high magnetic permeability by further regulating the average particle size D50 of the high entropy alloy powder to 15μm-75μm, so that the overall performance is better. If the particle size is too small, the hysteresis loss is difficult to further reduce, and the high cost of fine powder is not conducive to industrialization; if the particle size is too large, the surface area of ​​the high entropy alloy particles will be too small, affecting the coating effect, indirectly affecting the thermal conductivity of the magnetic core, and it will be difficult to reduce the eddy current loss in the particles, resulting in the loss of the magnetic core still being too high at high frequencies.

[0189] In summary, the present invention adopts a negative temperature coefficient, the composition of which satisfies the general formula Fe a Co b Ni c Cr d Al e High entropy alloy powder is used as magnetic powder. As the temperature increases, the resistivity of the alloy increases, thereby suppressing eddy current loss. After being coated with an inorganic insulating layer and an organic insulating layer, the two are coordinated to obtain a high entropy alloy soft magnetic composite material with high frequency, low loss and good heat resistance and heat dissipation performance, which can meet the needs of the electronic and electrical fields under high frequency and high temperature conditions.

[0190] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. A high entropy alloy soft magnetic composite material, characterized in that: The high entropy alloy soft magnetic composite material comprises a high entropy alloy powder, and an inorganic insulating layer and an organic insulating layer sequentially coated on the surface of the high entropy alloy powder; The composition of the high entropy alloy powder satisfies the general formula Fe a Co b Ni c Cr d Al e , wherein a, b, c, d and e represent the atomic percentages of the corresponding alloy elements, respectively, 20≤a=b=c≤25, 10≤d≤15, 15≤e≤25, and a+b+c+d+e=100.

2. The high entropy alloy soft magnetic composite material according to claim 1, characterized in that: In the high entropy alloy soft magnetic composite material, the inorganic insulating layer material is a one-dimensional structure; Preferably, the inorganic insulating layer material comprises aluminum nitride; Preferably, the inorganic insulating layer and the organic insulating layer are coupled and bonded via a coupling agent; Preferably, in the high entropy alloy soft magnetic composite material, the organic insulating layer material comprises organic silicone resin; Preferably, the organic silicon resin comprises silicon-containing aromatic acetylene resin or methylphenyl silicone resin; Preferably, the average particle size D50 of the high entropy alloy powder is 15 μm-75 μm.

3. A method for preparing a high entropy alloy soft magnetic composite material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) performing a first mixing of a high entropy alloy powder and an inorganic insulating layer material to obtain a first coated powder; (2) a solution containing an organic insulating layer material is mixed with the first coated powder for a second time, granulated to obtain a second coated powder, and pressed and annealed to obtain a high entropy alloy soft magnetic composite material; The composition of the high entropy alloy powder satisfies the general formula Fe a Co b Ni c Cr d Al e , wherein a, b, c, d and e represent the atomic percentages of the corresponding alloy elements, respectively, 20≤a=b=c≤25, 10≤d≤15, 15≤e≤25, and a+b+c+d+e=100.

4. The preparation method according to claim 3, characterized in that: The method for preparing the high entropy alloy powder in step (1) comprises: After mixing Fe powder, Co powder, Ni powder, Cr powder and Al powder, dry ball milling is performed to obtain the high entropy alloy powder; Preferably, the purity of the Fe powder, the Co powder, the Ni powder, the Cr powder and the Al powder is independently ≥ 99.8%; Preferably, the dry ball milling is performed under an inert atmosphere.

5. The preparation method according to claim 3 or 4, characterized in that: Based on the mass of the high entropy alloy powder, the mass of the inorganic insulating layer material in step (1) is 1wt%-5wt%; Preferably, the method of first mixing the high entropy alloy powder and the inorganic insulating layer material in step (1) comprises: After mixing the high entropy alloy powder and the inorganic insulating layer material, a solvent is added and wet ball milling is performed.

6. The preparation method according to claim 5, characterized in that: After the wet ball milling, the method further includes subjecting the wet ball milled powder to a first drying step, and then subjecting the powder to ultrasonic mixing with a solution containing a silane coupling agent, and then subjecting the powder to a second drying step to obtain a first coated powder; Preferably, in the solution containing a silane coupling agent, the silane coupling agent includes any one of vinyl silane, alkyl silane or amino silane, or a combination of at least two thereof; Preferably, based on the mass of the high entropy alloy powder, the mass of the silane coupling agent is 0.5wt%-2wt%; Preferably, in the solution containing the silane coupling agent, the solvent includes any one of anhydrous ethanol, methanol, ethylene glycol or acetone, or a combination of at least two thereof; Preferably, the ultrasonic mixing process also includes stirring.

7. The preparation method according to any one of claims 3 to 6, characterized in that: Based on the mass of the high entropy alloy powder, in the solution containing the organic insulating layer material in step (2), the mass of the organic insulating layer material is 0.8wt%-4wt%; Preferably, in the solution containing the organic insulating layer material in step (2), the solvent comprises any one of acetone, toluene or xylene, or a combination of at least two thereof; Preferably, the second mixing in step (2) comprises ultrasonic treatment, and the ultrasonic treatment process also includes stirring; Preferably, in the granulation process of step (2), the mesh size of the sieve used for sieving is 50-100 mesh; Preferably, after the granulation in step (2), the method further comprises subjecting the granulated powder to a third drying step.

8. The preparation method according to any one of claims 3 to 7, characterized in that: Before the pressing and forming in step (2), the method further comprises performing a third mixing of the second coated powder and a release agent; Preferably, based on the mass of the high entropy alloy powder, the mass of the release agent is 0.1wt%-0.3wt%; Preferably, the pressure of the compression molding in step (2) is 1500MPa-2000MPa; Preferably, the annealing temperature in step (2) is 700° C.-900° C.; Preferably, the annealing time in step (2) is 45 min-120 min; Preferably, the annealing in step (2) is performed under a protective atmosphere; Preferably, the protective atmosphere comprises a nitrogen atmosphere or an argon atmosphere.

9. The preparation method according to claim 3, characterized in that: The preparation method comprises the following steps: (1) Fe powder, Co powder, Ni powder, Cr powder and Al powder with a purity of ≥99.8% are mixed, and dry ball milled at a speed of 200 rpm to 600 rpm for 12 h to 24 h in an inert atmosphere to obtain a high entropy alloy powder with an average particle size D50 of 15 μm to 75 μm, wherein the composition of the high entropy alloy powder satisfies the general formula Fe a Co b Ni c Cr d Al e , where a, b, c, d and e represent the atomic percentages of the corresponding alloying elements, 20≤a=b=c≤25, 10≤d≤15, 15≤e≤25, and a+b+c+d+e=100; After mixing the high entropy alloy powder and the inorganic insulating layer material, a solvent is added, and wet ball milling is performed at a rotation speed of 100 rpm-200 rpm for 2h-6h to perform a first mixing, and the powder after wet ball milling is dried at 60°C-150°C for 30min-60min. After the first drying, the powder is ultrasonically mixed with a solution containing a silane coupling agent at a frequency of 20kHz-40kHz for ≥10min, and the ultrasonic mixing process also includes stirring. The powder after ultrasonic mixing is dried at 60°C-150°C for 30min-60min, and after the second drying, a first coated powder is obtained; Based on the mass of the high entropy alloy powder, the mass of the inorganic insulating layer material is 1wt%-5wt%; (2) ultrasonically treating the solution containing the organic insulating layer material and the first coated powder at a frequency of 20kHz-40kHz for ≥10min, wherein the ultrasonic treatment process also includes stirring, performing a second mixing, granulating and screening, the mesh number of the sieve is 50-100 mesh, and performing a third drying on the granulated powder to obtain a second coated powder; Based on the mass of the high entropy alloy powder, in the solution containing the organic insulating layer material, the mass of the organic insulating layer material is 0.8wt%-4wt%; After the release agent and the second coated powder are mixed for the third time, the mixture is pressed under a pressure of 1500 MPa-2000 MPa, and annealed at 700° C.-900° C. for 45 min-120 min in a protective atmosphere to obtain a high entropy alloy soft magnetic composite material; Based on the mass of the high entropy alloy powder, the mass of the release agent is 0.1wt%-0.3wt%.

10. An application of a high entropy alloy soft magnetic composite material, characterized in that: The high entropy alloy soft magnetic composite material according to claim 1 or 2, or the high entropy alloy soft magnetic composite material prepared by the preparation method according to any one of claims 3 to 9, is applied to magnetic electronic components.